2007
DOI: 10.1080/02571862.2007.10634779
|View full text |Cite
|
Sign up to set email alerts
|

Extractable soil phosphorus threshold values for dryland maize on the South African Highveld

Abstract: The principle objective of this study was to establish P fertilizer guidelines for dryland maize on the South African Highveld according to the sufficiency concept of soil extractable P. Data sets from nine different P fertilizer trials at various localities in the Free State, Gauteng, Mpumalanga and North West provinces were used. Different P treatments were applied for all trials in order to establish differences in extractable soil P levels, which were expected to have corresponding effects on maize yield. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…(1994). Recent work by Schmidt et al (2007) indicated that threshold values are related to the degree of leaching and silt-plus-clay content of the soil. For practical purposes they proposed threshold values ranging from 33.5 mg kg -1 for 13% silt-plus-clay to 14.6 mg kg -1 for 60% silt-plus-clay.…”
Section: Phosphorusmentioning
confidence: 99%
“…(1994). Recent work by Schmidt et al (2007) indicated that threshold values are related to the degree of leaching and silt-plus-clay content of the soil. For practical purposes they proposed threshold values ranging from 33.5 mg kg -1 for 13% silt-plus-clay to 14.6 mg kg -1 for 60% silt-plus-clay.…”
Section: Phosphorusmentioning
confidence: 99%
“…Expected relative maize yields in unfertilised soils may be around 40-50 % of potential yield according to data for critical levels from Nigeria (Adeoye and Agboola, 1985). Even lower relative yields may be expected based on data for Oxisols in Brazil (Smyth and Cravo, 1990) and data from South Africa (Schmidt et al, 2007). Below the 10 to 20 cm soil depth, the extractable P concentrations were generally around 2 mg kg -1 for both conservation and conventional tillage (Fig.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Therefore, P concentration was supposed to be low on the natural vegetation types with 250 mg kg -1 [38], and 500 mg kg -1 on cultivated land [39]. However, these assumptions are rather uncertain, because of the site specific high variability of soil phosphorus [40].…”
Section: Daily Particulate Phosphorus Inputmentioning
confidence: 99%